Strategi Penanganan Komunikasi Krisis Transportasi Publik di Era Digital: Studi Kasus Kecelakaan KA Argo Bromo Anggrek dan KRL Commuter Line di Stasiun Bekasi Timur - Wardana, Dadan; Afandiah, Ageng Wuri Rezeki (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze PT Kereta Api Indonesia’s crisis communication strategies in handling the accident involving the Argo Bromo Anggrek train and the KRL Commuter Line at Bekasi Timur Station on April 27, 2026. The study employs a descriptive qualitative approach, with analysis grounded in Anwar Arifin’s communication strategy theory, W. Timothy Coombs’ Situational Crisis Communication Theory (SCCT), William Benoit’s Image Restoration Theory (IRT), and Sherry Turkle’s perspectives on digital communication. The results of the study indicate that PT KAI implemented a crisis communication strategy that was prompt, empathetic, transparent, and adaptive through social media, press conferences, and public service announcements. This strategy successfully mitigated public panic, restored public trust, and strengthened the organization’s image amid the pressure of digital public opinion.